The man who came late to dinner. A sundial, a raven, and a missed dinner party on a mosaic at Tarsus. (2019) - Dunbabin, Katherine M. D.; Adak Adıbelli, Işık; Çavuş, Mehmet; Alper, Doğukan; ,
Abstract : In 2012, construction works at the traditional olive market at Tarsus, in Eski Ömerli district, revealed large-scale architectural remains of the Roman period; the construction works were halted and a salvage excavation was initiated by Tarsus Museum. The remains that appeared at the first stage of the excavations were interpreted as those of a reservoir from the Roman Imperial period, stretching along a N–S axis. On the E side, a structure projects from the E wall of the reservoir, containing a pool that collects water flowing from drainage pipes set in the reservoir's façade. The pool was extended in two stages in late antiquity. 1 Two metres north of this pool and 3 m from the E wall of the reservoir, the excavations revealed a mosaic pavement (9.73 x 5.05 m), apparently forming part of the floor of a building running parallel to the reservoir's wall (fig. 1).